PERILAKU MASYARAKAT TERHADAP HUTAN NAGARI, NAGARI PAKAN RABAA KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Nia Audina; yurni suasti; deded Chandra (JURNAL BUANA, 2017)
This study aims to determine the behavior of the community on the flora and fauna and community behavior in land use in the forage nagari Pakan Rabaa, Kecamatan Koto Parik Gadang Diateh, Kabupaten Solok Selatan. The data used to complete this study is the primary data. Primary data were obtained from direct interviews with Nagari Pakan Rabaa, Wali Nagari Pakan Rabaa, Head of Kerapatan Adat Nagari (KAN) of Pakan Rabaa, Chairman of Nagari Forest Supervisory Agency (LPHN) Pakan Rabaa. Data collection techniques in this study using observation techniques, interviews, and documentation. Data analysis techniques that is by way of data reduction, data presentation, and withdrawal of conclusions. The results of this research are: (1) There is deviation to nagari forest. The irregularities are logging of protected status ie Wood Merantih and Banio by timber agents and the persons concerned. People use dead wood to be used as fuel for cooking. Deviation on fauna also occurs in the nagari forest. Some communities catch protected animals such as Deer, Deer and Goat Forest. (2) Community behavior on land in the nagari forest is the community to expand the field by cutting wood and bush then burned